Leukocytosis Fluctuation Despite Clinical Improvement In Peritonsillar Infiltrate: A Case Report - Sabira Husna Ristyana; Iwan Setiawan Adji; Fadli Rizal Faqihudin (Persatuan Dosen Kesehatan Masyarakat, 2026)
Leukocytosis is an important indicator in assessing the inflammatory response to acute infections, including peritonsillar infiltrate, which represents an early stage preceding the formation of a peritonsillar abscess. However, an increased leukocyte count does not always correlate proportionally with clinical improvement. This case report presents an 11-year-old boy diagnosed with peritonsillar infiltrate, accompanied by odynophagia, mild trismus, and submandibular edema. Laboratory examinations revealed fluctuating leukocytosis, rising from 23,280/µL to 30,800/µL and then decreasing to 23,360/µL, despite significant clinical improvement. The patient initially showed a suboptimal response to ceftriaxone–metronidazole therapy but demonstrated marked improvement after the administration of meropenem. This phenomenon is presumed to result from the interplay between ongoing inflammatory activity, the pharmacologic effect of corticosteroids causing neutrophil demargination, and the physiological stress response during the healing phase. This case underscores the importance of a multidimensional interpretation of hematologic parameters when evaluating the success of therapy in acute infections and highlights the urgency of implementing antibiotic stewardship in response to increasingly complex patterns of antibiotic resistance.